Implementasi Sistem Monitoring Pengukuran pada Pembangkit Listrik Tenaga Mikrohidro Berbasis Arduino di Kampus PNUP Makassar - Mubarak, Husni; Gazali, Amal All; Aprilya, Putri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to design and implement an electrical parameter monitoring system for a Micro Hydro Power Plant (PLTMH) based on Arduino Uno. The system was developed by integrating current, voltage, and speed sensors to obtain real-time performance data of the power plant. The research employed an experimental method consisting of hardware and software design, system testing, and analysis of measurement data. The results indicate that the developed monitoring system is capable of measuring and displaying the main electrical parameters, namely voltage, current, and electrical power, continuously and in real time. Under the testing conditions, the maximum values obtained were 10.6 V for voltage, 0.16 A for current, and 1.7 Watts of output power at a water discharge of 32 L/min. These results demonstrate that the monitoring system performs properly and is able to represent the operational performance of the micro hydro power plant. Therefore, the system can be effectively utilized as a monitoring tool to support performance evaluation and management of the power generation system.